The sensitivity of the Kleihauer–Betke test for placental abruption. (February 2015) - Atkinson, A. L.; Santolaya-Forgas, J.; Matta, P.; Canterino, J.; Oyelese, Y.
Abstract The Kleihauer–Betke (KB) test evaluates fetal blood in the maternal circulation, and is often used when placental abruption is suspected. At our centre, it is the protocol to perform a KB test in all suspected cases of abruption. We carried out a retrospective study of all cases of abruption that occurred at our centre over 6 years. Of the 68 confirmed cases of placental abruption, only three had positive KB tests, giving a sensitivity of only 4.4%. Thus, in the overwhelming majority of cases of confirmed abruption, the KB test was negative. Our findings indicate that the KB test has poor sensitivity for placental abruption and should not be used in the detection of abruption.